Keragaman Jenis Khamir Penghasil Etanol yang Diisolasi dari Makanan Fermentasi di Kepulauan Riau - Sumerta, I Nyoman; Kanti, Atit (Perhimpunan Biologi Indonesia, 2017)
ABSTRACTInformation on genetic diversity of fermentative yeast which produce ethanol is very crucial in developing biofuel production in Indonesia. Research on ethanol producing yeasts is interest of many scientist. The objective of study was to reveal yeast diversity in Indonesian fermented foods that able to produce ethanol. The sample of fermented foods were collected in the traditional market in Karimun Besar Island, Kepulauan Riau. Yeast isolation was performed using serial dilution with direct plating and enrichment culture with glucose as carbon source. Fifteen of isolates were isolated and identified by amplification of D1/D2 region LSU 26S rDNA. Its ethanol production characteristic was analyzed base on fermentation activity and measurement with gas chromatography for ethanol content. The result revealed that 8 yeast species were found belong to Ascomycetous and grouped into 5 clades which are able to produce ethanol. The highest ethanol production was obtained by Saccharomyces cerevisiae Y15Kr107 (3.53%) followed by Torulaspora delbrueckii Y15Kr104 (1.63%), Saccharomyces cerevisiae Y15Kr093 (1.58%), Candida glabrata Y15Kr110 (1.4%), Torulaspora delbrueckii Y15Kr103 (1.29%), Candida glabrata Y15Kr108 (1%), Torulaspora globosa Y15Kr094 (0.92%), Kodamaea ohmeri Y15Kr096 (0.61%), and Pichia kudriavsevii Y15Kr106 (0.31%) Y15Kr105 (0.21%) Y15Kr109 (0.16%). Other yeasts strains did not produce ethanol but may play different role in fermentation process.Key words: yeast, fermented food, ethanol, Kepulauan Riau